Effect of Cr2O3 on the magnetic properties of magnetite-based glass-ceramics obtained by controlled crystallization of Fe-containing aluminoborosilicate glass. Issue 9 (August 2017) - Sandu, V.; Greculeasa, S.; Kuncser, A.; Nicolescu, M.S.; Kuncser, V.
Abstract: The phase structure and magnetic properties of magnetite-based glass-ceramics obtained by crystallization of Fe-containing boroaluminosilicate glass melts are presented. The use of Cr2 O3 as nucleating agent generated magnetite configurations showing a complex temperature dependence of the relaxation of the remanent magnetization. Specifically, the expected decrease in time of the remanent magnetization occurs only in a limited temperature range, whereas it increases at low and high temperatures (upward relaxation). We tentatively attribute these effects to the complex spin structure of the tiny magnetite nanoparticles, their complex size distribution and the interplay between the relaxation mechanisms in different temperature ranges.